2008
DOI: 10.1038/sj.bjc.6604293
|View full text |Cite
|
Sign up to set email alerts
|

Screening history of women with cervical cancer: a 6-year study in Aarhus, Denmark

Abstract: To identify possible weaknesses in cervical screening in Aarhus County, 10 years after the programme was introduced, screening histories were examined. A major problem for the screening programme was that 31% of women were never screened and 61% under-screened, the latter group being significantly dominated by older women and high-stage tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 8 publications
4
14
0
Order By: Relevance
“…13 In the United States, where screening is opportunistic, the proportion of cervical cancer cases aged 16-90 years old with no previous screening has been reported to be as low as 2.2%-7%, 14,15 with an increase in the proportion of unscreened or insufficiently screened women with increasing age. 16 In Europe, studies have reported that 25%-40% of cervical cancer cases have never been screened prior to their diagnosis, [17][18][19] and similarly to the United States, older women are reportedly less likely to have been screened F I G U R E 3 Results of cervical cytology tests obtained prior to a diagnosis of cervical cancer in 377 ever-screened women compared to younger women 19,20 ; however, this trend has been reported to decline over calendar time, as more women may have had the opportunity to be screened. 13 The incidence and mortality rates of cervical cancer are high in older Danish women.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the United States, where screening is opportunistic, the proportion of cervical cancer cases aged 16-90 years old with no previous screening has been reported to be as low as 2.2%-7%, 14,15 with an increase in the proportion of unscreened or insufficiently screened women with increasing age. 16 In Europe, studies have reported that 25%-40% of cervical cancer cases have never been screened prior to their diagnosis, [17][18][19] and similarly to the United States, older women are reportedly less likely to have been screened F I G U R E 3 Results of cervical cytology tests obtained prior to a diagnosis of cervical cancer in 377 ever-screened women compared to younger women 19,20 ; however, this trend has been reported to decline over calendar time, as more women may have had the opportunity to be screened. 13 The incidence and mortality rates of cervical cancer are high in older Danish women.…”
Section: Discussionmentioning
confidence: 99%
“…Other countries with national coverage of health care have the advantage of linking their cancer data with screening histories through pathology databases or other screening registries, which is much more conducive to this type of data collection. [26][27][28][29] However, despite barriers and the intensive work, the abstractors were able to pull 1.5 records on average for the women in the study who had been seen.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis revealed that part of the observed increase in CIN treatments derived from a county with a historically low compliance with follow‐up recommendations. In this county, about 35% of women with abnormal smears were not followed‐up according to the guidelines,34 and 26% of cervical cancer patients with recent abnormal findings were inadequately followed‐up 35. In 2006, a strategy aiming to facilitate the adherence to the follow‐up guidelines was introduced 34.…”
Section: Discussionmentioning
confidence: 99%